Neutrophil Extracellular Traps and Endothelial Dysfunction in Atherosclerosis and Thrombosis - Qi, Haozhe; Yang, Shuofei; Zhang, Lan (Frontiers in Immunology, 2017)
Cardiovascular diseases are a leading cause of mortality and morbidity worldwide. Neutrophils are a component of the innate immune system which protect against pathogen invasion; however, the contribution of neutrophils to cardiovascular disease has been underestimated, despite infiltration of leukocyte subsets being a known driving force of atherosclerosis and thrombosis. In addition to their function as phagocytes, neutrophils can release their extracellular chromatin, nuclear protein, and serine proteases to form net-like fiber structures, termed neutrophil extracellular traps (NETs). NETs can entrap pathogens, induce endothelial activation, and trigger coagulation, and have been detected in atherosclerotic and thrombotic lesions in both humans and mice. Moreover, NETs can induce endothelial dysfunction and trigger proinflammatory immune responses. Overall, current data indicate that NETs are not only present in plaques and thrombi, but also have causative roles in triggering formation of atherosclerotic plaques and venous thrombi. This review is focused on published findings regarding NET-associated endothelial dysfunction during atherosclerosis, atherothrombosis, and venous thrombosis pathogenesis. The NET structure is a novel discovery that will find its appropriate place in our new understanding of cardiovascular disease. In addition, NETs have high potential to be further explored toward much better treatment of atherosclerosis and venous thromboembolism in clinic.